Dental admissions in children under two years – a total‐population investigation. Issue 2 (13th February 2012) - Slack‐Smith, L.; Colvin, L.; Leonard, H.; Kilpatrick, N.; Read, A.; Messer, L. B.
Abstract: Background  There is a lack of literature describing dental admissions in children particularly very young children. This paper describes dental and oral cavity admissions and associated factors in children under two years of age using total‐population databases. Methods  The data used for this study were extracted from population‐based databases which are linkable with midwives' data collected on all births in Western Australia. Children born from 1980 to 1998 inclusive ( n = 459 831) were followed until two years of age including data on deaths, hospital admissions, birth defects and intellectual disability. Dental admissions (by ICD‐9 category) and associated factors were investigated. Results  There were 1513 dental admissions occurring in 1459 of the children up to the age of two years. Children were most frequently admitted under ICD‐9 category 521, which includes a hospital admission for dental caries (39% of all oral cavity admissions), followed by ICD‐9 category 528 (29%), which includes diseases of the oral soft tissues. Univariate analysis indicated that those with intellectual disability (OR 2.10, 95%CI 1.40–3.16), birth defect (1.74, 1.45–2.09), residing in a region without fluoridated water (2.15, 1.72–2.69) being male (1.14, 1.03–1.26), those from rural areas (2.29, 2.07–2.54) and Indigenous children (4.45, 3.91–5.05) were significantly more likely to have had a dental admission. Conclusion  Using total‐population data allowed us to describe the admissions in children under two years and associated factors while able to identify children with intellectual disability or birth defects.